1997
DOI: 10.1001/archinte.1997.00440260117015
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Attitudes Toward Detection of Heterozygous Familial Hypercholesterolemia

Abstract: The results indicated that a substantial proportion of persons with heterozygous FH had some degree of anxiety. A small minority regretted that they were informed of the diagnosis of heterozygous FH, however, and a majority were in favor of family screening for heterozygous FH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 31 publications
2
29
0
Order By: Relevance
“…2007). In our study, it was found that most people believed that anxiety would not be a barrier to genetic testing, whereas Andersen et al found that anxiety was expressed by 44% of the FH index cases and their relatives (Andersen et al 1997). …”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…2007). In our study, it was found that most people believed that anxiety would not be a barrier to genetic testing, whereas Andersen et al found that anxiety was expressed by 44% of the FH index cases and their relatives (Andersen et al 1997). …”
Section: Discussionmentioning
confidence: 52%
“…in their family (Andersen et al 1997). In a nationally representative sample of British residents, 69% of the sample was in favor of genetic testing for heart disease, and those participants with a family history of heart disease were even more interested in genetic testing (74%) (Sanderson et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…13 However, existing cascade screening programmes for FH have shown little, if any, long-term detrimental effects upon participants' quality of life. 11,14,15 …”
Section: Familial Hypercholesterolaemia (Fh) Cascade Screeningmentioning
confidence: 99%
“…133 Some young relatives prefer to have testing for the diagnosis of FH delayed, while others remain in a 'state of denial' and prefer not to be tested at all. 134,135 Screening also has the potential to lead to family discord, especially when children are asked by parents to avoid certain foods. The person conducting cascade testing should also be aware that there is debate about whether the probands should invite the relatives for testing or should provide the names of the relatives so that the screening programme can approach them for testing.…”
Section: Screening Relatives Of Fh Probandsmentioning
confidence: 99%